PELAKSANAAN PERJANJIAN ANTARA DINAS KESEHATAN KOTA PAYAKUMBUH DENGAN PT ANALISA SILA KARYA TENTANG REHAB PUSKESMAS IBUH MENURUT HUKUM PERDATA - Hanifah Fithriyah; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The agreement as described in Article 1313 of the Civil Code is an act in which one or more persons bind themselves to one or more persons. The cooperation agreement applies the provisions of Article 1320 of the Civil Code regarding the legal requirements of an agreement, where in the cooperation agreement there is an agreement between the parties which will give rise to rights and obligations for each party. This agreement will later become binding as law for the parties who make it in accordance with Article 1338 of the Civil Code. In this paper, the author discusses the implementation of the agreement between the Payakumbuh City Health Office and PT Analisa Sila Karya regarding the rehabilitation of the Ibuh Health Center regarding the rehabilitation of the Ibuh Health Center. The purpose of writing this thesis: First, to find out the implementation of the agreement between the Payakumbuh City Health Office and PT Analisa Sila Karya regarding the rehabilitation of the Ibuh Health Center according to civil law. Second, to find out the legal consequences that occurred according to the agreement between the Payakumbuh City Health Office and PT Analisa of Sila Karya regarding the rehabilitation of the Ibuh Health Center. Third, to find out the completion of the contract between the Ibuh Health Center and PT Analisa Sila Karya.The type of research conducted is empirical juridical, namely research on the effectiveness of the law, how the law operates in society. The author's suggestion, in this research, is to the first party as a commitment maker, namely the Payakumbuh City Health Office and the second party as a provider of goods and services who have entered into a cooperation agreement. Both parties must carry out the agreement in accordance with the contents of the agreement, PT Analisa Sila Karya must complete the work on time in accordance with the agreement and the Payakumbuh City Health Office also provides additional time if the rehabilitation work of the Ibuh Health Center has problems resulting in delays.